Crystal structure refinement, enhanced magnetic and dielectric properties of Na0.5Bi0.5TiO3 modified Bi0.8Ba0.2FeO3 ceramics. Issue 5 (1st April 2017) - Kaswan, Kavita; Agarwal, Ashish; Sanghi, Sujata; Rangi, Manisha; Jangra, Sandhaya; Kumar, Ajay
Abstract: (1-x) Na0.5 Bi0.5 TiO3 –x(Bi0.8 Ba0.2 FeO3 ) (x=0.5, 0.6, 0.7, and 0.8) ceramics were synthesized via solid state reaction method. Powder X-ray diffraction investigations performed at room temperature along with Rietveld analysis show all the composites to exhibit a rhombohedral distorted perovskite structure, described by space group R 3 c . Rietveld refinement confirmed a good agreement between observed and calculated intensities and a low value of goodness of fit (χ 2 ). Magnetic measurements were carried out at room temperature up to a field of 6 kOe. Magnetic properties of BBFO modified NBT ceramics are improved with a significant opening in the M–H hysteresis loop at room temperature. Remanent magnetization and coercive field increased with increase of BBFO concentration. The dielectric response of these samples was analyzed in the frequency range 10 Hz–7 MHz at different temperatures revealing a dispersion in dielectric constant (ε′) and in dissipation factor (tan δ) at lower frequencies. Both ε′ and tan δ increase with increase of BBFO content. The temperature dependence of frequency exponent ′s′ of power law suggests that quantum mechanical tunneling (QMT) model to be applicable at lower temperature and correlated barrier hopping (CBH) mechanism to be appropriate at higher temperature to describe the conduction mechanism in x=0.5 and x=0.6 samples. Further, with increase in BBFO content, the dielectric constant becomes more stable at higher frequencies and temperatures thereby improving the dielectric properties of the material.